2012
DOI: 10.5897/ijps11.1615
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarbonfibril in rice flour charcoal

Abstract: This paper presents the results of a study of nanocarbonfibrils in charcoals, which were prepared from rice flour with diameters of 90, 75 and 38 µm, respectively. The rice flours were carbonized for 30 min at a temperature of 600 to 800°C. The carbonized products were characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), Fourier transform infrared spectrometer (FTIR), energy dispersive X-ray spectrometer (EDS) and X-ray diffractometer (XRD). Nanocarbonfibrils with diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…These flour samples showed the peak at 2931 cm −1 was attributed to C-H bond stretching. These results were consistent with the research conducted by Mopoung, Sirikulkajorn, Dummun, and Luethanom (2012). The FTIR analysis indicated that the waste flour and rice flour showed absorption peaks in the same regions.…”
Section: Proximate Analysis Of Waste Floursupporting
confidence: 92%
“…These flour samples showed the peak at 2931 cm −1 was attributed to C-H bond stretching. These results were consistent with the research conducted by Mopoung, Sirikulkajorn, Dummun, and Luethanom (2012). The FTIR analysis indicated that the waste flour and rice flour showed absorption peaks in the same regions.…”
Section: Proximate Analysis Of Waste Floursupporting
confidence: 92%
“…The result of the surface area further indicated that carbonization followed by chemical activation resulted in activated carbons with high surface area. This is as a result of dehydration of the precursor by the activating agents [64]. The SEM micrograph for the activated carbon shows a broad porous surface (Fig.…”
Section: Characteristics Of the Adsorbentmentioning
confidence: 98%